Análise dos fatores organizacionais que influenciam a percepção de risco a uma tomada de decisão gerencial: estudo de caso - Siciliano, Rinaldo (2008)
The improvement of human performance and safety has been the subject of constant research, deemed essential to the role of organizations seeking excellence. For those involved in high-risk technology, as the segment of the oil and gas, should be the realization that efforts to control measures have been developed without, however, take into account different levels of occupational risk, situational aspects of organizational culture , components of safety control measures, among others. Among these findings are that human error has been identified as significant portion of the root causes of events such as unwanted failures, led by the "human factor" in these industries. Amid the "human factors", the perception of risk has been incorporated into the research goal of better understanding the interaction of all man-machine-organizational system, so much so that this interaction has acquired great value for inserting a secure process, no more should be practiced in isolation. The survey covers the perception element, as something inherent to cognitive abilities and attributes, the set of safety factors existing in an organization where there are gaps. Indicates that the gaps in process and safety may arise from the demands of management, indicators and decision making. In this regard, this paper discusses the use of control measures that tend to be used as indicators of safety. These measures generally do not consider human perception as a factor seen in the context of continuous and systemic organization. In order to sharpen the knowledge about the perception that planned actions can fail in pursuit of their goals, this research has been proposed in order to get gaps in perception between the management and operation using specific criteria that comprise the organizational culture, tied to decision making